The impact of Green Supply Chain Management (GSCM) on Green Consumption Intention (GCI): Mediating and Moderating Role of Green Image and Environmental Responsibility - Wong, Tze Jin; Nawaz, Muhammad Javid; Iqbal, Zafar; Iqbal, Shakir; Ali, Arshad; Qurat-ul-ain (Society of History and Cultural Studies, 2024)
This study endeavors to address the relationship between green supply chain management (GSCM) and green consumption intention(GCI), which are examined in this research, along with the moderating effect of environmental responsibility and the mediating role of green image. Even though consumers are becoming more environmentally concerned, a current study has been done to explain how GSCM projects affect customers' intentions, especially in Project based organization. To assess the suggested hypotheses, 210 employees of projects based organization participated in a survey methodology that used SPSS and PLS-SEM analyses. The results highlight the important role that GSCM plays in encouraging green consumption intentions; of particular significance is the mediation pathway that involves green image. Furthermore, the study shows that the relationship between green image and green consumption intentions is significantly shaped by environmental responsibility. Theoretical and managerial contexts examine the ramifications of these findings, highlighting the transformative potential of GSCM projects in promoting sustainable consumption structure. This study fills the gap in the literature by offering new perspectives for future research into consumer behavior and sustainable supply chain management in the construction sector.